A formação flautística no Conservatório Estadual de Música Padre José Maria Xavier: um estudo histórico. - Fernando Augusto Sales (2011)
This work focus on the research of the flutist formation of the State Conservatory of music Padre José Maria Xavier, in São João Del-Rei. Through the documents of the school was made a research which established the chronology of the flute school teachers since 1953, the beginning year of activities of the conservatory. Through biographies of teachers and students we could check the intimacy of them with the bicentenary orchestras of the city. And as a process of formation of a music school are presented the different ways of performance and studies of the students. The music in São João del-Rei is studied since the beginnings, passing mainly by the orchestras Lira Sanjoanense (1776) and the Orchestra Ribeiro Bastos (1790) which perform a role welcoming a lot of musicians and preserving the repertory of XVIII and XIX century. The repertory written by a lot of musicians for flute is presented and by the context of religious rituals is a way of having the flutists to perform in the city.